Prognostic importance of molecular-like classification in gastroesophageal junction tumors (Izmir Oncology Group [IZOG] study) - Özdemir, Özlem; Argon, Asuman; Yakan, Savaş; Salman, Tarık; AlacacIoğlu, Ahmet (Polish Journal of Pathology, 2021)
A comprehensive molecular classification was published in 2014 within The Cancer Genome Atlas (TCGA) to guide clinical approaches and treatment strategies. This study aimed to investigate the clinicopathological and prognostic importance of the classification using immunohistochemistry (IHC) and chromogenic in situ hybridization (CISH) to identify potential surrogate markers of molecular changes in gastroesophageal junction (GEJ) adenocarcinomas. A total of 52 GEJ adenocarcinomas were divided into five groups using IHC with MLH-1, E-cadherin, p53 and CISH with EBER: 1) microsatellite unstable (MSI: negative with MLH-1), 2) genomically stable tumors (GS: positive with p53), 3) chromosomally unstable tumors (CUN: negative with e-cadherin), 4) EBV+ tumors (EBV+: positive with EBER) and 5) unclassifiable (G-NOS: MLH-1 and e-cadherin positive with p53 and negative with EBER). The largest group consisted of 24 (46.2%) cases of CUN tumors. This group was followed by groups of GS with 14 (26.9%) cases, MSI with 7 (13.5%) cases, and EBV + with 3 (5.8%) cases, respectively. Although this classification was not associated with pathological features, it was found to be closely related to prognosis (p = 0.029). Patients with EBV+ tumors had the longest overall survival, followed by the G-NOS, MSI, CUN, GS groups.